Technical-tactical analysis of small combat games in male kickboxers: effects of varied number of opponents and area size - Ibrahim Ouergui; Slaheddine Delleli; Anissa Bouassida; Ezdine Bouhlel; Helmi Chaabene; Luca Paolo Ardigò; Emerson Franchini (BMC, 2021)
Abstract Background To handle the competition demands, sparring drills are used for specific technical-tactical training as well as physical-physiological conditioning in combat sports. While the effects of different area sizes and number of within-round sparring partners on physiological and perceptive responses in combats sports were examined in previous studies, technical and tactical aspects were not investigated. This study investigated the effect of different within-round sparring partners number (i.e., at a time; 1 vs. 1, 1 vs. 2, and 1 vs. 4) and area sizes (2 m × 2 m, 4 m × 4 m, and 6 m × 6 m) variation on the technical-tactical aspects of small combat games in kickboxing. Method Twenty male kickboxers (mean ± standard deviation, age: 20.3 ± 0.9 years), regularly competing in regional and national events randomly performed nine different kickboxing combats, lasting 2 min each. All combats were video recorded and analyzed using the software Dartfish. Results Results showed that the total number of punches was significantly higher in 1 versus 4 compared with 1 versus 1 (p = 0.011, d = 0.83). Further, the total number of kicks was significantly higher in 1 versus 4 compared with 1 versus 1 and 1 versus 2 (p < 0.001; d = 0.99 and d = 0.83, respectively). Moreover, the total number of kick combinations was significantly higher in 1 versus 4 compared with 1 versus 1 and 1 versus 2 (p < 0.001; d = 1.05 and d = 0.95, respectively). The same outcome was significantly lower in 2 m × 2 m compared with 4 m × 4 m and 6 m × 6 m areas (p = 0.010 and d = − 0.45; p < 0.001 and d = − 0.6, respectively). The number of block-and-parry was significantly higher in 1 versus 4 compared with 1 versus 1 (p < 0.001, d = 1.45) and 1 versus 2 (p = 0.046, d = 0.61) and in 2 m × 2 m compared with 4 m × 4 m and 6 × 6 m areas (p < 0.001; d = 0.47 and d = 0.66, respectively). Backwards lean actions occurred more often in 2 m × 2 m compared with 4 m × 4 m (p = 0.009, d = 0.53) and 6 m × 6 m (p = 0.003, d = 0.60). However, the number of foot defenses was significantly lower in 2 m × 2 m compared with 6 m × 6 m (p < 0.001, d = 1.04) and 4 m × 4 m (p = 0.004, d = 0.63). Additionally, the number of clinches was significantly higher in 1 versus 1 compared with 1 versus 2 (p = 0.002, d = 0.7) and 1 versus 4 (p = 0.034, d = 0.45). Conclusions This study provides practical insights into how to manipulate within-round sparring partners' number and/or area size to train specific kickboxing technical-tactical fundamentals. Trial registration This study does not report results related to health care interventions using human participants and therefore it was not prospectively registered.